δ18 values in Holocene and modern ice wedges and AMS radiocarbon ages of ice wedges of the enclosing peat, Lorino site, Eastern Chukchi Peninsula - Yurij K Vasil extquotesinglechuk; Nadine A Budantseva; Alla Constantinovna Vasil extquotesinglechuk; Alexey A Maslakov; Igor V Tokarev; Jessica Yurevna Vasil extquotesinglechuk (PANGAEA, 2025)
The present study focuses on syngenetic ice wedges exposed in the peatland near the Lorino site on the eastern coast of the Chukchi Peninsula. The study extquotesingles goal was to find out when peatlands formed and ice wedges grew. We accomplished this by applying radiocarbon dating to peat and organic micro-inclusions extracted directly from ice wedges, analyzing oxygen isotope ratios in ice wedge samples to determine their age, and estimating the mean January air temperature at that time. At the Lorino site on the eastern coast of the Chukchi Peninsula, pre-Holocene (more than 12 cal ka BP) and early Holocene onsets of peatland accumulation were recorded. Every 14C date that has been determined for the peat falls between 14.2 and 9.9 cal ka BP. Ice wedge formation in the peatland occurred during the Northgrippian period of the Holocene, about 7.7 to 6.6 cal ka BP. Early Holocene deep thawing and mixing of the previously existing polygonal peatland may explain the older age of the enclosing peat (compared with the ice wedges) and age inversions. A new generation of ice wedges was formed after permafrost aggraded, which occurred at 8 cal ka BP. Most of the obtained δ^1?O values for the studied Holocene ice wedges are in the range of -18 to -15 extperthousand, in modern ice veinlets, δ^1?O values are generally higher and range from –16.8 to –12.9 extperthousand. The lowest δ^1?O values, from -21 to -18.1 extperthousand, were obtained for the fragment of Late Pleistocene ice wedge under the peatland. The estimated mean January air temperature during the Northgrippian stage of the Holocene ranged between –27 and -23°C, and at the end of the Late Pleistocene it varied between -32 and -26°C, according to the paleotemperature signal evaluation based on the δ^1?O values in ice wedges at the Lorino site.